Urazowe uszkodzenie mózgu = Traumatic brain injury - Bartłomiej Kulesza; Jakub Litak; Cezary Grochowski; Jacek Kulesza; Adam Nogalski (Kazimierz Wielki University, 2016)
Kulesza Bartłomiej, Litak Jakub, Grochowski Cezary, Kulesza Jacek, Nogalski Adam. Urazowe uszkodzenie mózgu = Traumatic brain injury. Journal of Education, Health and Sport. 2016;6(12):215-221.eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.197104 http://ojs.ukw.edu.pl/index.php/johs/article/view/4044 https://pbn.nauka.gov.pl/sedno-webapp/works/763747       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 07.12.2016.       Urazowe uszkodzenie mózgu Traumatic brain injury Bartłomiej Kulesza1, Jakub Litak2, Cezary Grochowski2, Jacek Kulesza3, Adam Nogalski1   1 Katedra i Klinika Chirurgii Urazowej i Medycyny Ratunkowej Uniwersytetu Medycznego w Lublinie2 Katedra i Klinika Neurochirurgii i Neurochirurgii Dziecięcej Uniwersytetu Medycznego w Lublinie3 Oddział Neurochirurgiczny, Szpital Specjalistyczny w Sandomierzu lek. med. Bartłomiej Kulesza1,lek. med. Jakub Litak2,lek. med.  Cezary Grochowski2,dr n. med. Jacek Kulesza3,dr hab. n. med. Adam Nogalski1   Streszczenie Urazowe uszkodzenie mózgu (TBI)  nie jest właściwie jedną chorobą,  ale obejmuje szeroki zakres zmian w funkcjonowaniu mózgu lub inną ewidentną patologią mózgu spowodowaną zadziałaniem siły zewnętrznej.  TBI jest często określane mianem "cichej epidemii".  Szacuje się że w Europie każdego roku z powodu jakieś formy TBI cierpi 2,5 miliona osób.  Patologiczny mechanizm TBI można podzielić na dwie fazy: pierwotne i wtórne uszkodzenie mózgu.  Są różne skale służące do oceny poszkodowanych po urazach, w przypadku urazów głowy największe znaczenie ma skala stanu świadomości Glasgow (GCS).  Najczęściej stosowana skala do oceny wyników leczenia chorych po TBI jest skala wyników leczenia Glasgow (GOS).  Rokowanie po TBI jest z reguły niekorzystne, można je próbować oszacować uwzględniając wiele czynników lub korzystając z dwóch kalkulatorów prognostycznych dostępnych w Internecie. Słowa kluczowe: urazowe uszkodzenie mózgu, epidemiologia, skala, rokowanie Abstract Traumatic brain injury (TBI) is not just one disease, but includes a wide spectrum alteration in brain function, or other evidence of brain pathology caused by external force. TBI is often referred to as "the silent epidemic". In Europe, it is estimated approximately 2,5 milion people suffer from some form of TBI.  The pathological mechanism of TBI is divided into two phases: primary and secondary brain injury. There are various scales to assess victims after injuries,  in case of head injuries the most important is Glasgow Coma Scale (GCS). The most common scale used to evaluate the results of treatment of patients after TBI is Glasgow Outcome Scale (GOS). The prognosis after TBI is generally unfavorable, there are a few factors which can try to assess outcomes or there are two prognostic calculators available on the Internet. Key words: traumatic brain injury, epidemiology, scale, outcome